The Influence of The School Principal's Leadership on The Work Motivation of Teachers At SDN Magetan 1 - Mulyanto, Nanang (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
A leader is essentially someone who has the ability to influence others in their work by using power. Meanwhile, the principal consists of two words, namely the principal and the school. The word head can be interpreted as the chairman or leader in an organization or an institution and a school is an institution where it is a place to receive and give lessons. Motivation is a factor that encourages a person to perform a certain deed or activity. While work is a number of physical and mental activities to do something work. In order for the implementation of work motivation to be implemented properly, it is necessary to have the leadership of the principal who has the ability to nurture its members to support the teaching and learning process in schools. This study was conducted to examine the Influence of Principal Leadership on the Work Motivation of Teachers of SDN Magetan 1 with the aim of knowing how the Influence of Principal Leadership at SDN Magetan 1, how the Motivation of Teachers' Work at SDN Magetan 1. This type of research uses quantitative research. And the data collection is carried out by the method of questionnaires, observations, and documentation. Then the data is analyzed using statistical formulas, namely: percentage formula and product moment formula and added with regression formula.